The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.5380/avs.v11i3.7427
|View full text |Cite
|
Sign up to set email alerts
|

DESENVOLVIMENTO PONDERAL, BIOMETRIA TESTICULAR E QUALIDADE SEMINAL DE TOUROS NELORE (Bos taurus indicus) CRIADOS EXTENSIVAMENTE NA REGIÃO CENTRO-OESTE DO BRASIL

Abstract: Com o objetivo de avaliar características testiculares e seminais de touros Nelore criados extensivamente em uma região de clima tropical de savana, 271 animais foram divididos em quatro classesde idade (C1, 17 a 20 meses; C2, 21 a 24 meses; C3, 25 a 30 meses e C4, 31 a 36 meses) e submetidos à avaliação andrológica. O peso vivo (PV) foi obtido imediatamente antes da colheita do sêmen, realizandose a aferição do comprimento (COMP) e largura (LARG) dos testículos, assim como da circunferência escrotal (CE). O v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
11

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 3 publications
1
5
0
11
Order By: Relevance
“…Similar results were obtained by Viu et al (2006) with values of -0.06, 0.08, -0.27, -0.13 and -0.26 for testicular shape with progressive motility, sperm vigor, major defects, minor defects and total defects, respectively.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Similar results were obtained by Viu et al (2006) with values of -0.06, 0.08, -0.27, -0.13 and -0.26 for testicular shape with progressive motility, sperm vigor, major defects, minor defects and total defects, respectively.…”
Section: Resultssupporting
confidence: 74%
“…Dias et al (2007) reported no significant values for correlations between testicular shape and scrotal circumference. However, Viu et al (2006) reported higher values (0.32 and 0.43 between testicular shape with scrotal circumference and testicular volume, respectively), showing that selection for increased scrotal circumference would respond positively correlated to the testicular shape, indicating the possibility of indirect gains for spherical testicular shapes. Conflicting values are normal because it is a categorical variable with few classes, providing high ranges of values for scrotal circumference and testicular volume so that mean values for each class of testicular shape did not differ, except when there was not a normal distribution.…”
Section: Resultsmentioning
confidence: 88%
“…This effect is observed in the reduced age at puberty and sexual maturity of zebu animals even in those herds that are raised extensively (Brito et al 2004;Martins et al 2011;Pinho et al 2013). This genetic improvement can also be observed in the increased scrotal circumference of selected herds (Viu et al 2006;Martins et al 2011;Pinho et al 2013). The use of the scrotal circumference as the main parameter for the selection of bulls for breeding involves selecting the animals with higher sperm production and an increased testicular volume, which directly implies changes in the functional morphology of this organ and justifies the need for periodic updates of these measurements to characterize the evolution of the morphometric indexes of the testicular parenchyma (Unanian et al 2000;Andreussi et al 2013).The volumetric proportion of Leydig cells in the intertubular tissue and the quantitative parameters directly related to the seminiferous tubule, such as the tubule diameter, the thickness of the seminiferous epithelium and the tubule length (total length and length per gram of testicular parenchyma), are positively correlated with spermatogenic activity, providing information regarding the level of spermatogenic activity and constitute indicators of this activity in investigations involving testicular function (França and Russell 1998;Paula et al 1999).…”
Section: Introductionmentioning
confidence: 79%
“…Entretanto, correlações favoráveis e de alta magnitude entre VOLT, CTE, CTD, LTE, LTD e CE indicam que a CE é parâmetro adequado para ser utilizado nos programas de seleção para predição do tamanho dos testículos em animais da raça Nelore. Viu et al (2006) encontraram valor de correlação entre CE e volume testicular de 0,81, e sugeriram que a seleção para precocidade sexual por meio da CE levaria à resposta correlacionada no volume testicular. Unanian et al (2000) observaram que a CE é mais influenciada pela largura do que pelo comprimento dos testículos, o que poderia comprometer essa associação em animais de testículos longos.…”
Section: Resultsunclassified